2013
DOI: 10.5755/j01.eee.19.2.3473
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithm Based Palm Recognition Method for Biometric Authentication Systems

Abstract: Biometric authentication systems are steadily becoming a solution to wide number of authentication and identity management problems. Unique parts of human body that can be recognized and used as a mean to identify a person include fingerprints, iris, lips, etc. Though fingerprint and facial recognition systems are most widely used and developed, most of the systems and methods are slow or require expensive technical equipment. In this article genetic algorithm based palm recognition method is proposed, which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Cenys et al in 2013 suggested a new palm print recognition method that used the GA as a recognition method that does not need any special equipment and can be used in fast palm recognition for identity management and personal authentication. This method is faster by 10 times more than the manual methods, the manual method requires 220 seconds while this method required only 25 seconds or less with the same accuracy which was 96% by using CASIA Dataset [10].…”
Section: Review Of Literaturementioning
confidence: 93%
See 1 more Smart Citation
“…Cenys et al in 2013 suggested a new palm print recognition method that used the GA as a recognition method that does not need any special equipment and can be used in fast palm recognition for identity management and personal authentication. This method is faster by 10 times more than the manual methods, the manual method requires 220 seconds while this method required only 25 seconds or less with the same accuracy which was 96% by using CASIA Dataset [10].…”
Section: Review Of Literaturementioning
confidence: 93%
“…Table 3 shows the results of the test phase in the proposed hybrid method (DSO-SVM) when the values of the coefficients are as (HOG -cell size) at (8,16,32), (HOG -block size) at (2), Initial, (population of Dolphin) at (10,30,50) and (Max no. iteration) at (10,30,50).…”
Section: % Precision (9)mentioning
confidence: 99%
“…In paper [ 15 – 17 ] the authors proposed a genetic algorithm based palm recognition method for authentication process. The authors suggested that fingerprint and facial recognition systems are slow and required more expensive technical equipment, while palm recognition method did not require special equipment and could be used in systems where fast detection is required.…”
Section: Related Workmentioning
confidence: 99%
“…The system achieved 95.00% accuracy. A. Cenys et al [4] presented a model that uses genetic algorithm for palm recognition. Several measures of a palm of a person are made on 25 palm print, this method had a 92-96% reliability.…”
Section: Introductionmentioning
confidence: 99%